Toxicity and therapeutical impacts of Bee venom (Apis mellifera L.) on Nile tilapia juvenile (Oreochromis niloticus) - Mohammed F. El Basuini; Haitham M. Ramadan; Abdelaziz M. El-Hais; Mohamed A.A. Zaki; Nourhan M. Kamel; Islam I. Teiba; Emad H. El-Bilawy; Mohamed Reda Badr; Mohamed Fathy Abdel-Aziz; Akram Ismael Shehata (Aquaculture and Fisheries)
Bee venom (BV) has been widely studied for its therapeutic properties in various medical applications. However, its effects on aquatic organisms, particularly Nile tilapia (Oreochromis niloticus), remain poorly understood, particularly concerning toxicity and therapeutic impacts. This study investigated the effects of bee venom (BV) injection on Nile tilapia (O. niloticus) by examining growth, feed efficiency, biometric parameters, whole-body chemical analysis, and the activity of antioxidant enzymes in the liver. Nile tilapia juveniles were injected with BV at doses of 0, 3, 6, 9, and 12 mg/kg of fish weight. Observations were made on the 14th day post-injection (DPI). No significant differences were found in growth, feed utilization, survival rate, biometric indices, and whole-body composition among the BV dosage groups. Similarly, the activity of intestinal enzymes (amylase, protease, and lipase) showed no significant changes. However, the study revealed a time-dependent response of antioxidant enzymes (SOD, CAT, and GPx) in the liver, with activity peaks on the 4th and 6th DPI. On the 14th DPI, fish injected with BV at doses of 3, 6, and 9 mg/kg exhibited higher antioxidant enzyme activities compared to the control and the highest dosage group (12 mg/kg). These results imply the presence of potential adaptive antioxidant activity and a favorable influence on the health and immune responses of Nile tilapia following BV injection. Notably, the effects appear to vary with the dose, influencing both antioxidant enzyme activities and immunity. Further research is warranted to explore the long-term effects of BV exposure and its potential therapeutic applications in aquaculture.